Rifampicin resistance and mortality in patients hospitalised with HIV-associated tuberculosis - Ruan Spies; Charlotte Schutz; Amy Ward; Avuyonke Balfour; Muki Shey; Mark Nicol; Rosie Burton; Bianca Sossen; Robert Wilkinson; David Barr; Graeme Meintjes (AOSIS, 2022)
Background: Patients with HIV and drug-resistant tuberculosis (TB) are at high risk of death. Objectives: We investigated the association between rifampicin-resistant TB (RR-TB) and mortality in a cohort of patients who were admitted to hospital at the time of TB diagnosis. Method: Adults hospitalised at Khayelitsha Hospital and diagnosed with HIV-associated TB during admission, were enrolled between 2013 and 2016. Clinical, biochemical and microbiological data were prospectively collected and participants were followed up for 12 weeks. Results: Participants with microbiologically confirmed TB (n = 482) were enrolled a median of two days (interquartile range [IQR]: 1-3 days) following admission. Fifty-three participants (11.0%) had RR-TB. Participants with rifampicin-susceptible TB (RS-TB) received appropriate treatment a median of one day (IQR: 1-2 days) following enrolment compared to three days (IQR: 1-9 days) in participants with RR-TB. Eight participants with RS-TB (1.9%) and six participants with RR-TB (11.3%) died prior to the initiation of appropriate treatment. Mortality at 12 weeks was 87/429 (20.3%) in the RS-TB group and 21/53 (39.6%) in the RR-TB group. RR-TB was a significant predictor of 12-week mortality (hazard ratio: 1.88; 95% confidence interval: 1.07-3.29; P = 0.03). Conclusion: Mortality at 12 weeks in participants with RR-TB was high compared to participants with RS-TB. Delays in the initiation of appropriate treatment and poorer regimen efficacy are proposed as contributors to higher mortality in hospitalised patients with HIV and RR-TB.